2004
DOI: 10.15763/issn.2374-7781.2004.25.0.241-263
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Setting, Innovation, and State Gay Rights Policy: An Event History Analysis

Abstract: By using gay rights policy as a framework, this research attempts to link the process of agenda-setting with the diffusion of innovation across the United States both theoretically and empirically. Based on independent variables that reflect both agenda-setting and diffusion, it is hypothesized that stronger predictive models will result from linking agenda-setting to innovation. While many scholars have found state-specific variables to be the strongest predictors of gay rights policy adoption, by joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…LGBT federal employees' perceived discrepancy of equitable workplace treatment on so many fronts demands that the federal government as an employer change to become more fair, open, and supportive to all its employees. Past research has examined how policies have affected the inclusion of gay men and lesbians in federal government including how veteran's preference affects the number of gay men that hold federal jobs (Lewis, 2013), and how policy has supported the denial of security clearance and the exclusion of gay men and lesbians from federal government (Colvin, 2004;Johnson, 1994Johnson, , 2004Lewis, 2001). Research has also explored whether LGBTs face employment discrimination (Cech & Pham, 2017;Federman & Elias, 2017;Lewis & Pitts, 2011, 2017.…”
Section: Report Thatmentioning
confidence: 99%
“…LGBT federal employees' perceived discrepancy of equitable workplace treatment on so many fronts demands that the federal government as an employer change to become more fair, open, and supportive to all its employees. Past research has examined how policies have affected the inclusion of gay men and lesbians in federal government including how veteran's preference affects the number of gay men that hold federal jobs (Lewis, 2013), and how policy has supported the denial of security clearance and the exclusion of gay men and lesbians from federal government (Colvin, 2004;Johnson, 1994Johnson, , 2004Lewis, 2001). Research has also explored whether LGBTs face employment discrimination (Cech & Pham, 2017;Federman & Elias, 2017;Lewis & Pitts, 2011, 2017.…”
Section: Report Thatmentioning
confidence: 99%
“…This global divergence in adoption of rights for the LGBTQ+ community begs the question of why some countries try to ensure a discrimination-free workplace and "fulfillment of citizen duties" (e.g., contributing to the economy) regardless of sexual orientation while others do not. Previous research has found various reasons, local conditions such as activism, urbanization, religiosity but also international problem pressure (e.g., Ayoub and Page 2020;Ayoub 2015;Colvin 2004). This problem pressure can be administered through IOs and other advocacy groups, but also other policymakers, which then ultimately leads to policy diffusion.…”
Section: Setting Up a Timelinementioning
confidence: 99%
“…Although a lot of evidence points to the influence of local culture and conditions on the introduction of these policies, it has to be mentioned that the internal pressure to implement these policies is often higher in industrialized, urban regions due to the higher chances of a more diverse community (Colvin 2004).…”
Section: Previous Researchmentioning
confidence: 99%